Edukasi Kesehatan Gigi Dan Mulut Pada Anak Usia Pra Sekolah Di Paud Sekar Mekar Mojosongo Surakarta - Siswanto Pabidang; Eka Vicky Yulivantina; Rizka Fatmawati (Institut Teknologi dan Bisnis Semarang, 2024)
Background: Brushing teeth is one way to maintain healthy teeth and mouth. By brushing your teeth, you will maintain oral and dental hygiene, as well as preventing the formation of dental caries and dental disease. If teeth do not receive treatment, tooth decay will occur because teeth are body tissue that is easily damaged. So health education is carried out by modeling how to brush teeth so that children can concentrate and learn how to brush teeth properly and correctly. Research Objective: To provide dental and oral health education to pre-school children at PAUD Sekar Mekar Mojosongo Surakarta. Research Method: This research uses an action research method with a participatory action program approach. The sample in this study was PAUD Sekar Mekar Mojosongo Surakarta. The stages of this research consist of preparation, implementation and evaluation stages. The preparation stage begins with identifying the problem through interviews with parents and PAUD teachers and observations, preparing materials and leaflets. The implementation stages are delivering the material, practicing toothbrushing. Research Results: The results of the study showed that there was an increase in children's teeth brushing skills after being given education about dental and oral health to preschool aged children at PAUD Sekar Mekar Mojosongo Surakarta